Removal of Dye Acid Red 1 from Aqueous Solutions Using Chitosan-iso-Vanillin Sorbent Material - Abbad, Eman Al; Alakhras, Fadi (Universitas Pendidikan Indonesia, 2020)
Sorption of Acid Red 1 (AR1) from aqueous solutions utilizing low-cost sorbent material; (chitosan-iso-vanillin) is studied under batch conditions. The remaining concentrations of the azo dye are measured at Î»max = 546 nm by UV spectrophotometric method. Langmuir data reveal that the maximum removal capacity was 555.556 mg/g at pH 3. Freundlich isotherm represents the best fitting model on the removal of AR1 using chemically modified chitosan verifying the sorption takes place on heterogeneous surfaces with multilayer adsorption. Kinetic studies of the sorption process revealed that intraparticle diffusion is not only the rate-determining step but also a chemical reaction takes place as well. The results indicate that high sorption rapidness with almost 90% achieved within 90 min. Thermodynamic investigations suggest that the process favours an exothermic nature. The polymer utilized in the present study is being considered as a feasible sorbent material for the removal of AR1 from waste effluent.